Pemberdayaan Bagi Ibu-Ibu Melalui Pembuatan Jamu Tradisional Untuk Menambah Pendapatan Keluarga Menghadapi Masa New Normal - Sarlota A. Ratang (UNIVERSITAS CENDERAWASIH, 2022)
Almost all the countries have warned their citizens to not move outside their home if there is no urgent needed. Except, for those who have to go out and their activities cannot be done from home. Currently, we are starting to face the new normal era, where it can change our behavior to carry out normal activities but by implementing health protocols to prevent the transmission of Covid-19. Even if few need to do activities outside the home, it takes a good body condition and a strong immune. Many people believe that ginger or turmeric can help cure Covid-19 or those infected with the Corona Virus. Since there is a lot of free time at home, it is a good chance for both mothers and teenagers to make traditional herbal medicine that is currently being sought by the community in increasing their immune system to prevent this corona virus. So this activity focuses on making herbal drinks with attractive packaging. The target of the training participants as previously planned was 25 women around the activity location. Due to the situation during the pandemic that we could not collect more than 20 mothers, we were only able to collect 18 mothers. This figure shows that this training/socialization activity can be said that the target of participants reaching 95% can be said to be successful.